Rainfall characteristics of Pampa river basin, Kerala: A time series analysis - Mayaja, N.A and Srinivasa, C.V (International Journal of Innovative Research in Advanced Engineering (IJIRAE), 2014)
Kerala, one of the smallest States of South India, is blessed with forty-four rivers. The holy river of Pampa is the third largest river in the State of Kerala, 176km long with a catchment area of 2235Sq.km. Recurring tropical monsoon floods during every season is one of the perennial problems experienced in this river basin. Substantial damages including loss of human life and properties and also total destruction of the crops due to frequent floods are common features of this river basin. Hence understanding general rainfall trend in the river basin and its underlying features are very vital in meaningfully understanding the flood phenomena and its socio-economic impacts. The present study evaluates the general trend of rainfall in the Pampa river basin, utilising the data collected from five gauging stations. The time series of monthly and annual rainfalls for the past three decades have been analysed using statistical techniques. Standard statistical criteria have been employed to identify the models in the analysis. Significant changes have been observed in the basin rainfall features – both seasonal and annual rainfall. The changing rainfall pattern observed in this study and their socio-economic impacts have been discussed.